Análise de um programa de práticas expressivas através da arte em uma escola de ensino básico - Barreira, Dulcinéia Beatriz (2014)
The school space is a multiple place where social contact situations arise . A place where people that have different familiar culture are found every day in search of formal education . In our society , where many social problems appear , the school can fulfill an important role in the human formation by offering some teaching that can emphasize the sensitive development, joining several knowledge fields and encouraging the social and emotional abilities . According to texts of National Curriculum Analyses , the education must be committed to the citizenship and this means that it regards the social and environmental views as reflection .For this reason , we must analyze the education that deals with human activities that develop sensitivity and emotion seriously : the art and the appearance . It‟s comprehensible that the education that has the contributing art can help the formation of a better human society . Therefore, it‟s not about the art-education , but an appearance education that encourages opportunities of experiences in the world , to act in the world , to form meanings and then to know the world and to know yourself in it . This study analyzes a program of meaningful activities through the Art in an elementary school and this search has the objective to contribute to the human formation. Ten workshop s were carried out to teach teachers how to use these resources of arts to encourage the students to develop their sensitive view . People in this research are young teachers that work in a private school. They are really important people that make the culture exist . The used method was an intervention research that has involving acts and this method developed a program of important workshop with planned activities to match speculative concept . The evaluation of the program was carried out during the workshop . Concluding the research , some advance was found in the pedagogical practice as well as the importance of arts for the students and the appearance education for the teachers,furthermore the respect is something that needs to be present daily and it can be present in arts .